2011
DOI: 10.1128/jcm.01421-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Molecular Techniques for Typing Pseudomonas aeruginosa Isolates in Sputum Samples from Patients with Cystic Fibrosis

Abstract: Monitoring the emergence and transmission of Pseudomonas aeruginosa strains among cystic fibrosis (CF) patients is important for infection control in CF centers internationally. A recently developed multilocus sequence typing (MLST) scheme is used for epidemiologic analyses of P. aeruginosa outbreaks; however, little is known about its suitability for isolates from CF patients compared with that of pulsed-field gel electrophoresis (PFGE) and enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR). As pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 46 publications
(44 reference statements)
3
87
0
Order By: Relevance
“…Patients who had isolates with discrepant PFGE profiles between FE and RE samples underwent multilocus sequence typing (MLST) to determine if relatedness existed despite changes in PFGE profiles, using a method developed by Curran et al (22). The procedure followed methods from previously published works (23)(24)(25). Sequences were compared to those publically available at the P. aeruginosa MLST online database (http://pubmlst.org/paeruginosa/) to identify allele and sequence types.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who had isolates with discrepant PFGE profiles between FE and RE samples underwent multilocus sequence typing (MLST) to determine if relatedness existed despite changes in PFGE profiles, using a method developed by Curran et al (22). The procedure followed methods from previously published works (23)(24)(25). Sequences were compared to those publically available at the P. aeruginosa MLST online database (http://pubmlst.org/paeruginosa/) to identify allele and sequence types.…”
Section: Methodsmentioning
confidence: 99%
“…This population included 107 patients with chronic P. aeruginosa infection and 6 patients with transient infection. Of those included in the cohort, 72 (63%) patients are currently active within the CACFC cohort, 12 (11%) patients were transferred to another CF clinic, and 29 (26%) patients experienced respiratory failure and either received a life-saving lung transplant (24) or succumbed to CF (5). Among the members of the cohort, 101 (89%) patients had received prior care at a pediatric CF care center, and 12 were adults diagnosed with CF late in life, among which 9 received care only at CACFC.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Following DNA extraction, isolates were confirmed as P. aeruginosa by a duplex real-time PCR assay before performing DNA fingerprinting using the enterobacterial repetitive intergenic consensus (ERIC)-PCR typing technique [19,20]. Cluster analysis and genotype allocation of ERIC-PCR fingerprints were performed using FPQuest TM software (version 4.5; Bio-Rad Laboratories Pty Ltd, Hercules, CA, USA) as described previously [20].…”
Section: Genotypingmentioning
confidence: 99%
“…Several studies have shown Rep-PCR to have good correlation with PFGE results but, in general, with slightly less discriminatory power and less reproducible (Kidd et al, 2011).…”
Section: Rep-pcrmentioning
confidence: 99%